Effects of fast versus slow-releasing hydrogen sulfide donors in hypertension in pregnancy and fetoplacental growth restriction - Zochio, Gabriela Palma [UNESP]; Possomato-Vieira, Jose Sergio [UNESP]; Chimini, Jessica Sabbatine [UNESP]; da Silva, Maria Luiza Santos [UNESP]; Dias-Junior, Carlos Alan [UNESP] (Springer Nature, 2019)
Hydrogen sulfide (H2S) is a vasorelaxant gas with therapeutic potential in several diseases. However, effects of H2S donors in hypertensive pregnancy complicated by feto-placental growth restriction are unclear. Therefore, we aimed to examine and compare the effects of fast-releasing H2S donor (sodium hydrosulfide—NaHS) and slow-releasing H2S donor (GYY4137) in hypertension-in-pregnancy. Pregnant rats were distributed into four groups: normal pregnancy (Norm-Preg), hypertensive pregnancy (HTN-Preg), hypertensive pregnancy + NaHS (HTN-Preg + NaHS), and hypertensive pregnancy + GYY4137 (HTN-Preg + GYY). Systolic blood pressure, plasma H2S levels, fetal and placental weights, number of viable fetuses, litter size, and endothelium-dependent vasodilation were examined. Also, oxidative stress was assessed in placenta. We found that GYY4137 attenuated hypertension on gestational days 16 and 18, while NaHS presented antihypertensive effect only on gestational day 18. GYY4137, but not NaHS, increased plasma H2S levels. Greater fetal and placental weights were found with GYY4137 than NaHS treatment. Also, HTN-Preg + NaHS presented further reductions in placental weights when compared to HTN-Preg group. Number of viable fetuses and litter size presented no significant changes. GYY4137 reduced placental oxidative stress caused by hypertension, while greater increases in oxidative stress were found in HTN-Preg + NaHS than HTN-Preg group. Hypertensive pregnancy caused impaired endothelium-dependent vasodilation, while GYY4137 and NaHS treatments blunted endothelial dysfunction. Endothelium-dependent vasodilation was completely blocked by the nitric oxide synthase inhibitor. We conclude that slow-releasing H2S donor GYY4137 is advantageous compared with fast-releasing H2S-donor NaHS to attenuate hypertension-in-pregnancy and to protect against feto-placental growth restriction and oxidative stress.
Keywords: Hydrogen sulfide donors; Hypertensive pregnancy; Rats; Vasodilation